Experimental Research of Constructive Parameters of Drum Pile of Shovel Type Pile (Texas Journal of Multidisciplinary Studies, 2023)
The article discusses the modeling of an elastic bond in the process of cleaning weed impurities from two or more raw cotton flies. Graphs of the dependence on time are plotted at different angles of inclination over the surface of the mesh surface of raw cotton bats, as well as changes in the efficiency coefficient when cleaning raw cotton at two different angular velocities of each bat of raw cotton over time. From the analysis of the obtained graphs according to the theoretical study, it is possible to achieve the effective use of the mesh surfaces of the raw cotton cleaner from small weeds to increase the cleaning efficiency